Efficient Implementation of the Europe 2020 Strategy Goals: Is Social Equality Achievable Reality or Myth Perhaps? - Michaela Stanickova (Institute of Economic Research (IER), 2017)
Economic crisis hit all the European Union Member States hard, the impact of crisis varied considerably. The low growth performance in the EU has increased concerns regarding an increasing wage dispersion, income inequality at large, and social exclusion in line with poverty. Inequality should be seen as a cornerstone of both sustainable and inclusive growth under the Europe 2020 Strategy. Social inequality in the EU is a very real problem which hampers sustainable economic growth. The purpose of this study is to introduce evaluation of social development convergence and divergence trend between EU28 Member States in the context of the Europe 2020 Strategy. The study gives an outline of the issues of labour market and income disparities and poverty. Policy-makers must be clear about what social objectives they are aiming to achieve, therefore special attention is paid to headline national goals of the Europe 2020 Strategy. The main tasks of this study is to assess social dimension and inequalities problems in the EU27 by applying Data Envelopment Analysis method, resp. time-series dynamic efficiency analysis in the form of output-oriented Malmquist Productivity Index. This study contain changes of key social equality indicators related to the Europe 2020 Strategy and compares objectives and general outlines of period 2010-2015, as well as its impact on national economics and living conditions. Results contain elements of typology premises of the EU28 and point to a large diversity in inequality patterns, as author observe both increases and decreases in inequality at the EU level. Recent changes in social inequality have been associated with the business cycle, particularly with the accessibility of the labour market and, of course, with income inequality. Additionally the development challenges are discussed for improvement of the socioeconomic well-being of the EU27 and to avoid social disparities.
Keywords: C67; E24; E61; O52; P51; 330; DEA Method; Economic Crisis; EU28; Europe 2020 Strategy; Social Inequality